2006
DOI: 10.1021/nl0622449
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Transistor Using a Highly Ordered Conjugated Polymer as the Channel

Abstract: Field-effect transistor structures based on polydiacetylene (PDA) derivatives have been fabricated. Monolayer channels of UV polymerized pentacosa-10,12-diynoic ethanolamide exhibit modulation of source-drain current on application of a gating voltage. Comparison of the two-dimensional crystal morphology of this material with several closely related derivatives that show no gating suggests that a high degree of alignment and order in the polymer chains is necessary for the observed transistor action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…[7,8] Polydiacetylenes have also been used to fabricate monolayer FETs, again, with performance being far from ideal. [9] Although, charge transport behaviors of small-molecule-based n-channel FETs as a function of active layer thickness were shown previously, [10] no examples have been reported to date for polymer-based n-channel monolayer semiconductors. Recent studies have shown that n-type semiconducting polymers exhibit very attractive charge transport properties, [11] with electron mobilities of ∼0.2 cm 2 V −1 s −1 reported for the polymer poly{[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene)} (P(NDI2OD-T2), Polyera ActivInk N2200) in a top-gate FET architecture and using PMMA as gate dielectric.…”
Section: Doi: 101002/adma201103800mentioning
confidence: 93%
“…[7,8] Polydiacetylenes have also been used to fabricate monolayer FETs, again, with performance being far from ideal. [9] Although, charge transport behaviors of small-molecule-based n-channel FETs as a function of active layer thickness were shown previously, [10] no examples have been reported to date for polymer-based n-channel monolayer semiconductors. Recent studies have shown that n-type semiconducting polymers exhibit very attractive charge transport properties, [11] with electron mobilities of ∼0.2 cm 2 V −1 s −1 reported for the polymer poly{[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene)} (P(NDI2OD-T2), Polyera ActivInk N2200) in a top-gate FET architecture and using PMMA as gate dielectric.…”
Section: Doi: 101002/adma201103800mentioning
confidence: 93%
“…181 Polymerization creates linear polydiacetylene chains that terminate at domain edges or defects, with HOMO-LUMO gaps that decrease with increasing chain length, 154 and conductivities that increase substantially (up to 1000×) with iodine doping. 180 Films of polymerized pentacosa-10,12-diynoic ethanolamide exhibit source–drain modulation when a gate bias is applied, in contrast to less-ordered polymerized films, 182 suggesting the importance of aligning 1D features for applications in devices.…”
Section: One-dimensional Assembliesmentioning
confidence: 99%
“…Though desorption is clearly a problem for future devices, if the nanowires are in fact being picked up by the local probe, then it is possible that PDA-based devices not probed by STM would still work. This may explain the success of PDA-based transistors in recent reports [5,16]. It should also be noted that PDA nanowire desorption effects observed here can interfere with the observation of scanning tunneling spectroscopy (STS) data.…”
Section: B Desorption and Reordering Processesmentioning
confidence: 56%
“…Furthermore, PDA nanowires can desorb due to the STM tip [4]. Understanding PDA nanowire behavior is important for applications such as PDA monolayer transistors [5]. Here we use STM to analyze PDA nanowires on highly-ordered pyrolytic graphite (HOPG) and molybdenum disulfide (MoS 2 ) in order to understand the influence of the substrate on the electronic behavior of these structures.…”
Section: Introductionmentioning
confidence: 99%